1988
DOI: 10.3758/bf03327315
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial functions in the rat following injuries to striate, peristriate, and parietal neocortical sites

Abstract: The influenee oflesions located generaIly within four regions of the rat's posterior neocortex upon the aequisition and retention of two-choiee visual discriminations was assessed using a Thompson-Bryant apparatus. The ability to distinguish visual patterns was tested by utilizing stimuli eomposed of 45° versus 135 0 alternating blaek and white stripes (both total and local luminanee eues were eontroIled). "Brightness" discrimination was assessed by using blaek and white eard discriminanda. Posterior parietal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Our data add further weight to the argument that Krieg's (1946) area 7 in rat represents a true homologue of PPC in the monkey, sharing many common features (Kolb & Walkey, 1987; McDaniel & Wall, 1988). It would be interesting to know whether other primate deficits such as judgment of relative spatial position (Newcombe, Ratcliff, & Damasio, 1987; Pohl, 1973) are deficient in parietal rats and whether subdivisions exist within parietal cortex, as is the case in the monkey (Hyvarinen & Shelepin, 1979).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Our data add further weight to the argument that Krieg's (1946) area 7 in rat represents a true homologue of PPC in the monkey, sharing many common features (Kolb & Walkey, 1987; McDaniel & Wall, 1988). It would be interesting to know whether other primate deficits such as judgment of relative spatial position (Newcombe, Ratcliff, & Damasio, 1987; Pohl, 1973) are deficient in parietal rats and whether subdivisions exist within parietal cortex, as is the case in the monkey (Hyvarinen & Shelepin, 1979).…”
Section: Discussionsupporting
confidence: 65%
“…Surface diagrams of lesions are shown in Figures 1 (unilaterals) and 2 (bilaterals), and a coronal reconstruction of a typical unilateral lesion is shown in Figure 3. The region of cortex removed in all cases included Krieg's area 7 (Krieg, 1946) and the cortical regions identified as parietal by previous investigators who used anatomical and behavioral methods (Kolb & Walkey, 1987; McDaniel & Wall, 1988). Although the results of these previous studies showed some variability, the area that all investigators agree represents the parietal field lies on (and extends posteriorly to) the rostrocaudal midpoint of the hemisphere (see Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomical proximity of the visual and the posterior parietal cortices, which underlies functional relationships, supports the view that visuospatial processing is important (e.g., McNaughton, Leonard, & Chen, 1989; Miller & Vogt, 1984). Moreover, McDaniel and Wall (1988) showed that damage to the rat's posterior parietal cortex results in severe deficits in visuospatial discrimination tasks. However, the lack of deficit concerning the reaction to the novel object in the group PPC rats of the present study suggests that simple visual tasks, with no spatial component, are not sufficient to induce deficits in PPC rats.…”
Section: Discussionmentioning
confidence: 99%
“…One straightforward explanation is that the rats were impaired in perceiving or in organizing the perception of the spatial relationships between landmarks or objects (Kolb, 1990). Although experimental evidence in favor of this hypothesis is limited, its plausibility is supported by the importance of cortico-cortical connections between the APC and the visual areas (Miller & Vogt, 1984;Torrealba, Olavarria, & Carrasco, 1984;Kolb & Walkey, 1987) and by the results of behavioral studies (McDaniel, & Wall, 1987;McNaughton, Leonard, & Chen, 1989). However, the present results suggest that the overall function of the APC cannot be understood without taking into account a "kinesthetic component."…”
Section: Discussionmentioning
confidence: 99%